Argumentative style a pragma-dialectical study of functional variety in argumentative discourse - Eemeren, F. H. van (Frans Hendrik), 1946- (Argumentation in context ;, 2022)
"Argumentative Style discusses the various ways in which the defence of a standpoint is given shape in argumentative discourse. In this innovative study the new notion - 'argumentative style' - introduced for this purpose is situated in the theoretical framework of the pragma-dialectical approach to argumentation. This means that the choices involved in utilising a particular argumentative style do not only concern the presentational dimension, but also the topical selection and the audience adaptation of the strategic manoeuvring taking place in the discourse. In identifying the functional variety of the argumentative styles utilised in the political, the diplomatic, the legal, the facilitatory, the academic, and the medical domain, the point of departure is that these argumentative styles manifest themselves in the discourse in the argumentative moves that are made, the dialectical routes that are chosen and the strategic considerations that are brought to bear"--